2003
DOI: 10.1074/jbc.m308770200
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of an Intramolecular Hydrogen Bond in Differential Recognition of Inhibitory Acceptor Analogs by Human ABO(H) Blood Group A and B Glycosyltransferases

Abstract: Human ABO(H) blood group glycosyltransferases GTA and GTB catalyze the final monosaccharide addition in the biosynthesis of the human A and B blood group antigens. GTA and GTB utilize a common acceptor, the H antigen disaccharide ␣-L-Fucp-(132)-␤-D-Galp-OR, but different donors, where GTA transfers GalNAc from UDP-GalNAc and GTB transfers Gal from UDP-Gal. GTA and GTB are two of the most homologous enzymes known to transfer different donors and differ in only 4 amino acid residues, but one in particular (Leu/M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 11 publications
2
25
0
Order By: Relevance
“…Initial designs of inhibitors of GTA and GTB were made in the absence of any structural information concerning GTs and consisted of chemical modification of hydroxyl groups on the central galactose residue of HA-octyl (12,13). These studies have provided some of the few GT⅐inhibitor complexes available (11). In the present study, both enzymes have been shown to form an overwhelming number of interactions with the Gal residue such that its location in the active site is reproduced regardless of the other substituted saccharides.…”
Section: Dominance Of the Gal Residue And Generation Of Prototypic Inmentioning
confidence: 91%
See 1 more Smart Citation
“…Initial designs of inhibitors of GTA and GTB were made in the absence of any structural information concerning GTs and consisted of chemical modification of hydroxyl groups on the central galactose residue of HA-octyl (12,13). These studies have provided some of the few GT⅐inhibitor complexes available (11). In the present study, both enzymes have been shown to form an overwhelming number of interactions with the Gal residue such that its location in the active site is reproduced regardless of the other substituted saccharides.…”
Section: Dominance Of the Gal Residue And Generation Of Prototypic Inmentioning
confidence: 91%
“…This pattern has also been seen in inhibitory analogs of the H antigen, where the galactose residue analog dominates binding, and modification of specific points on the galactose residue can lead to effective inhibition (11)(12)(13).…”
mentioning
confidence: 94%
“…Crystallization-All proteins were crystallized using conditions different from those reported previously (10,19,33,35,38,39). Whereas the first crystals of GTB were grown from relatively low protein concentrations (ϳ8 -15 mg/ml) and as a mercury derivative, the crystals in this paper were initially generated from higher protein concentrations (ϳ60 -75 mg/ml).…”
Section: Construction Of the Synthetic Glycosyltransferase Chimericmentioning
confidence: 99%
“…Elucidation of the details of substrate recognition would allow the development of new inhibitors for the treatment of microbial diseases (5), genetic ailments such as diabetes (6), and cancer (7). The generation of inhibitors of the blood group A and B synthesizing glycosyltransferases GTA 2 and GTB have been reported (8,9), including an inhibitor-bound structure (10).…”
mentioning
confidence: 99%
“…The glycosyltransferase GTA transfers the N-acetylgalactosaminyl monosaccharide residue from UDP to Gal O3 of the H antigen [minimal epitope Fuc-(1!2)Gal] with retention of the axial stereochemistry to generate the human blood group A antigen and is a model enzyme for studying the retaining glycosyltransfer mechanism (Alfaro et al, 2008;Lee et al, 2005;Letts et al, 2007;Nguyen et al, 2003;Patenaude et al, 2002;Persson et al, 2007;Schuman et al, 2007Schuman et al, , 2010Seto et al, 1999). Evaluation of hydrogenbonding partners and amino-acid protonation states is critical for understanding the catalytic mechanisms of GTA and indeed of all retaining glycosyltransferases.…”
Section: Introductionmentioning
confidence: 99%